Association of maternal mineral status with the risk of preterm birth: a retrospective cohort study - Hong, Sumiao; Jiang, Nan; Lin, Guankai; Wang, Quqing; Xu, Xiaoyang; Shi, Xinrui; Zhou, You; Wen, Xiaoting; Sun, Baochang; Wang, Hexing; Huang, Min; Wang, Jiwei; et al. (Frontiers in Nutrition, 2024)
Background: There has been a gradual increase in the proportion of preterm birth in China during the past several decades. Maternal malnutrition is a significant determinant for preterm birth. Nevertheless, comprehensive studies investigating serum mineral levels during pregnancy associated with preterm birth remain scarce. This study aims to assess the associations between maternal serum mineral levels and the risk of preterm birth. Methods: This retrospective cohort study of 18,048 pregnant women used data from a tertiary hospital in China from January 2016 to December 2022. Demographic data and serum mineral concentrations in the second and third trimesters of mothers were collected from the hospital information system. Analysis was performed using restricted cubic splines and logistic regression models. Results: The proportion of preterm birth in this study was 6.01%. Phosphorus (P for overall = 0.005; P for nonlinear = 0.490; OR (95%CI) = 1.11 (1.04, 1.18)) and chlorine (P for overall = 0.002; P for nonlinear = 0.058; OR (95%CI) = 1.11 (1.03, 1.19)) showed a significant positive correlation with preterm birth in a linear fashion. Furthermore, serum levels of potassium (P for nonlinear < 0.001), sodium (P for nonlinear = 0.004), and magnesium (P for nonlinear < 0.001) exhibited non-linear relationships with the risk of preterm birth. Conclusions: Serum levels of some minerals during pregnancy were associated with the risk of preterm birth among pregnant women. In addition to commonly recognized micronutrients such as folic acid, iron, and vitamin D, healthcare providers should also pay attention to the levels of these minerals during pregnancy.